Ferric iron uptake into cardiomyocytes of β-thalassemic mice is not through calcium channels - Sirinart Kumfu (2018)
Iron-overload cardiomyopathy is a major cause of death in thalassemic patients. However, pathways of non-transferrin-bound iron (NTBI) uptake into cardiomyocytes under iron-overload conditions are still controversial. We previously demonstrated that Fe 2+ uptake in thalassemic cardiomyocytes is mainly mediated by T-type calcium channels (TTCCs). However, direct evidence regarding Fe 3+ uptake, the other form of NTBI, in thalassemic cardiomyocytes has never been investigated. Hearts from genetic-altered β-thalassemic mice and adult wild-type (WT) mice were used for cultured ventricular cardiomyocytes. Blockers for L-type calcium channel (LTCC), TTCC, transferrin receptor1 (TfR1), and divalent metal transporter1 (DMT1) were used, and quantification of cellular iron uptake was performed by the acetoxymethyl ester of calcein fluorescence assay. Cellular uptake of Fe 3+ under iron-overload conditions in cultured ventricular myocytes of thalassemic mice was greater than that of WT cells (P < 0.01). The iron chelator, deferoxamine, could prevent Fe 3+ uptake into cultured cardiomyocytes. However, blockers of TfR1, DMT1, LTCC, and TTCC could not prevent Fe 3+ uptake into cardiomyocytes. Our findings indicated that, unlike Fe 2+ , Fe 3+ uptake in cultured thalassemic cardiomyocytes is not mainly mediated by TfR1, DMT1, LTCC, and TTCC, suggesting that another alternative pathway could play a major role in Fe 3+ uptake in thalassemic cardiomyocytes. © 2013 Informa Healthcare USA, Inc.